The Role of the Human Mirror Neuron System in Supporting Communication in a Digital World - Dickerson, Kelly; Gerhardstein, Peter; Moser, Alecia (Frontiers in Psychology, 2017)
Humans use both verbal and nonverbal communication to interact with others and their environment and increasingly these interactions are occurring in a digital medium. Whether live or digital, learning to communicate requires overcoming the correspondence problem: There is no direct mapping, or correspondence between perceived and self-produced signals. Reconciliation of the differences between perceived and produced actions, including linguistic actions, is difficult and requires integration across multiple modalities and neuro-cognitive networks. Recent work on the neural substrates of social learning suggests that there may be a common mechanism underlying the perception-production cycle for verbal and nonverbal communication. The purpose of this paper is to review evidence supporting the link between verbal and non verbal communications, and to extend the hMNS literature by proposing that recent advances in communication technology, which at times have had deleterious effects on behavioral and perceptual performance, may disrupt the success of the hMNS in supporting social interactions because these technologies are virtual and spatiotemporal distributed nature.